EFFECT OF MAGNITIZED WATER ON COMMON CARP CYPRINUS CARPIO REARING IN DIFFERENT SALINITY CONCENTRATIONS - & Jumaa, Alrudainy (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
The present study was conducted to determine the effect of magnetized water on common carp Cyprinus carpio rearing in different salinity concentrations. The experiment was divided into four treatments using magnetized with 1500 gauss for each treatment, first as control with tap water, second treatment using water with 2 mg/l, third and fourth treatments with 3 and 4 mg/l respectively for 8 weeks. Results of the experiment indicated some variations between treatments as it seen sharp significant decrease (P≤0.05) in pH, dissolved O2 proportional with increasing salinity concentration but just remain within the accepted values for breeding common carp fish, meanwhile there are no significant differences in blood picture except in PCV which record significant decrease (P≤0.05) in fourth treatment. In contrast, blood ions noticed to record significant increase (P≤0.05) related proportionally with increasing salinity concentration. The survival ratio for is 100%. This study is confirmed that magnetized water could improve breeding and growth of common carp in the rivers or in water at mid concentrated salinity relatively for increasing magnetized with the time.